2007
DOI: 10.1021/ja0650394
|View full text |Cite
|
Sign up to set email alerts
|

Proton Assisted Insensitive Nuclei Cross Polarization

Abstract: This communication presents a solid-state NMR 15 N-13 C polarization transfer scheme applicable at high B 0 and high MAS frequencies, requiring moderate r.f. powers (~50 kHz 13 C/ 15 N) and mixing time (1-6 ms). The sequence, PAIN-CP, involves the abundant nearby protons in the heteronuclear recoupling dynamics, and provides a new tool for obtaining long distance 15 N-13 C contacts. It should be of major interest for biomolecular structural studies.Polarization transfer 1-15 between different nuclear species m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
216
1
1

Year Published

2009
2009
2011
2011

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 165 publications
(221 citation statements)
references
References 39 publications
3
216
1
1
Order By: Relevance
“…2 69 We restricted our investigation to zeroth-order dipolar recoupling sequences that produce a zeroth-order recoupled dipolar Hamiltonian, which are the ones typically used to obtain accurate internuclear distance measurements. We specifically avoided the treatment of proton-driven spin diffusion, [70][71][72] DARR/RAD, [73][74][75] homonuclear TSAR 22,23 techniques and MIRROR 25 recoupling, which perform polarization transfer via higher-order mechanisms that are more tolerant to dipolar truncation effects in multiple-spin systems, as shown previously, 22,51 but typically yield ambiguous distance constraints due to the complexity of the mechanisms.…”
Section: A Dipolar Truncation In Homonuclear Recoupling Schemes: Nummentioning
confidence: 99%
See 1 more Smart Citation
“…2 69 We restricted our investigation to zeroth-order dipolar recoupling sequences that produce a zeroth-order recoupled dipolar Hamiltonian, which are the ones typically used to obtain accurate internuclear distance measurements. We specifically avoided the treatment of proton-driven spin diffusion, [70][71][72] DARR/RAD, [73][74][75] homonuclear TSAR 22,23 techniques and MIRROR 25 recoupling, which perform polarization transfer via higher-order mechanisms that are more tolerant to dipolar truncation effects in multiple-spin systems, as shown previously, 22,51 but typically yield ambiguous distance constraints due to the complexity of the mechanisms.…”
Section: A Dipolar Truncation In Homonuclear Recoupling Schemes: Nummentioning
confidence: 99%
“…In this publication we focus primarily on zeroth-order sequences. Second-order or higher-order recoupling sequences [22][23][24][25] have different properties because they contain cross terms between two interactions and the effective coupling constants depend on both interactions.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, we found that the TSAR mechanism 35 constitutes an excellent choice to transfer the polarization from 15 N (residue i) to neighboring 13 C atoms in a bidirectional way (i.e., to residues i À 1 and i þ 1). 2D PAIN-CP spectra (Figure 4a) can be acquired in a relatively short experimental time (1À2 days), leading to highly resolved 15 NÀ 13 C spectra.…”
mentioning
confidence: 96%
“…18,19 Recently, a number of different methods were demonstrated as useful for providing long-range distance restraints for protein structure determination. 14,[20][21][22] Among them there are two promising approaches: proton assisted recoupling (PAR) and proton assisted insensitive nuclei cross polarization (PAIN-CP), which are based on a more general third spin assisted recoupling (TSAR) mechanism. 14,22 Notably, these new recoupling methods have been used to solve the largest solid-state nuclear magnetic resonance (SSNMR) protein structure reported to date (i.e., .…”
Section: Introductionmentioning
confidence: 99%
“…14,[20][21][22] Among them there are two promising approaches: proton assisted recoupling (PAR) and proton assisted insensitive nuclei cross polarization (PAIN-CP), which are based on a more general third spin assisted recoupling (TSAR) mechanism. 14,22 Notably, these new recoupling methods have been used to solve the largest solid-state nuclear magnetic resonance (SSNMR) protein structure reported to date (i.e., . 12 These techniques have also been applied to the challenging case of 15 N-15 N correlation spectroscopy and also demonstrated as one of the few pulse sequences able to provide long distance restraints in uniformly 13 C and 15 N labeled proteins in the ω r /2π > 50 kHz spinning frequency regime.…”
Section: Introductionmentioning
confidence: 99%